Quality Alterations in Fresh and Reheated Edible Oils: A Comparative Assessment Across Bagmati Province, Nepal - Sharma, Shubha; Thapa, Ratna Bahadur; Poudel, Bhoj Raj; Shrestha, Sabina (Damak Campus Journal, 2025)
The purpose of this study was to assess the qualitative and physicochemical properties of fresh, packaged, and reheated mustard oil samples collected from various locations in Bagmati Province, Nepal, to evaluate the impact of repeated heating and commercialization on oil quality. Six oil samples, including pure mustard oil (Brassica juncea), commercially packaged oils, and oils repeatedly heated in households and food shops, were analyzed. Standard methods from the Association of Official Analytical Chemists (AOAC) and the American Oil Chemists’ Society (AOCS) were used to measure acid value (AV), peroxide value (PV), saponification value (SV), ester value (EV), free fatty acid content (FFA%), and totox value (TV).The pure mustard oil sample closely matched standard quality values, while commercial and reheated oils exhibited elevated AV, PV, and TV, indicating oxidative and hydrolytic degradation. SV and EV decreased with repeated heating. The most deteriorated sample, collected from a doughnut shop, had the highest acid and peroxide values. These results highlight public health risks associated with adulterated and repeatedly heated oils, emphasizing the need for stricter regulatory oversight and increased consumer awareness.